2020
DOI: 10.3389/fpls.2020.572237
|View full text |Cite
|
Sign up to set email alerts
|

Construction of High-Quality Rice Ribosome Footprint Library

Abstract: High-throughput sequencing of ribosome footprints precisely maps and quantifies in vivo mRNA translation. The ribosome footprint sequencing has undergone continuing development since its original report. Here we provide a detailed protocol for construction of high-quality ribosome footprint library of rice. Rice total polysomes are isolated with a modified low ionic polysome extraction buffer. After nuclease digestion, rice ribosome footprints are extracted using SDS method followed by column purification. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…However, in rice, we observed that the vast majority of RPFs are 26–28nt in length, particularly RPFs of 27nt (Figure 1B). This unique feature was also observed in a previous study, in which a high-quality rice ribosome footprint library was constructed (Yang et al ., 2020). In total, 96.0% of RPFs could be mapped to annotated coding region (CDS), while the remaining RPFs were almost equally distributed in 5’UTR, 3’URT and intron (Figure 1C).…”
Section: Resultssupporting
confidence: 79%
“…However, in rice, we observed that the vast majority of RPFs are 26–28nt in length, particularly RPFs of 27nt (Figure 1B). This unique feature was also observed in a previous study, in which a high-quality rice ribosome footprint library was constructed (Yang et al ., 2020). In total, 96.0% of RPFs could be mapped to annotated coding region (CDS), while the remaining RPFs were almost equally distributed in 5’UTR, 3’URT and intron (Figure 1C).…”
Section: Resultssupporting
confidence: 79%
“…Polysomes were isolated by the method described by Yang et al [ 73 ]. Briefly, about 1 g of pulverized NB or SR86 shoots in liquid nitrogen was transferred to a 15-mL nuclease-free centrifuge tube with 5 mL ice-cold polysome extraction buffer (PEB) [100 mM Tris-HCl (pH 8.0), 40 mM KCl, 20 mM MgCl 2 , 2% (V/V) polyoxyethylene-10-tridecyl ether, 0.2% (W/V) deoxycholic acid, 1 mM DTT, 100 μg mL − 1 cycloheximide and 10 U mL − 1 DNaseI] and mixed well.…”
Section: Methodsmentioning
confidence: 99%
“…The filtrate was subjected to rRNA removal with the Ribo-Zero rRNA Removal Kit for Plant Leaf (MRZPL1224, ILLUMINA, USA). Finally, RPFs around 28–30 nt were recovered by PAGE purification as described previously [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations